Medical undergraduate primary care teaching across the UK: what is being taught?. Issue 1 (2nd January 2017) - Boon, Veronica; Ridd, Matthew; Blythe, Andrew
Abstract: Background : All UK medical schools use primary care settings to deliver their undergraduate courses. However there is no national undergraduate curriculum for primary care and it is thought that the learning objectives of primary care teaching vary considerably between medical schools. Aim : The overall aim was to establish what is being taught within and by primary care across UK medical schools. We did this by collating learning objectives from the primary care department at each school. In order to categorise and compare the list of learning objectives from each school we mapped the learning objectives to the postgraduate curriculum of the Royal College of General Practitioners (RCGP). Design and setting : Cross sectional survey sent to heads of teaching of primary care at all 32 UK medical schools. Method : GP teacher handbooks for primary care modules at each medical school were requested. Information was extracted based on key headings from the RCGP postgraduate curriculum. Results : Topics taught by primary care at all medical schools include: consulting and communication skills, leading and working in teams, and developing yourself and others. Novel topics, taught at a few medical schools include: learning disability, genetics and multi-morbidity. The majority of medical schools address aspects of over half of the RCGP postgraduate curriculum headings in their learning objectives for primary care. Conclusion : This project provides valuable information about primary care teaching at an undergraduate level across the UK. Although it confirms widespread variation in learning objectives, it also highlights considerable common ground and opportunities for sharing teaching resources between schools.